Analisis dan Perancangan Simulasi Enkripsi dan Dekripsi pada Algoritma Steganografi untuk Penyisipan Pesan Text pada Image menggunakan Metode Least Significant Bit (LSB) Berbasis Cryptool2 - Nofita Rismawati; Muhamad Femy Mulya (LPPM, 2019)
Security and confidentiality of data is the central aspect of an information system so that it can only be accessed by the owner of the information or interested user. In sending data, without the existence of a technique of concealing important information, it will be very easy for people who do not have access rights/interests to know the contents of the information. Steganography is the art and science of hiding secret messages in other messages so that the contents of the secret message cannot be traced. In this study, steganography technic is implemented by using the Least Significant Bit (LSB) method, modifying less significant bits or the last bit in one byte of data by using text messages as a storage medium. The purpose of this study was to analyze and design an encryption and decryption simulation for the insertion of text messages in an image by using the steganography algorithm using the Least Significant Bit (LSB) method, so that it would secure the text messages sent by the sender to the receiver by inserting the text message into an image both in the format * .jpg, * .bmp and * .png. The software will be used to simulate steganography using free program (Open Source) Cryptool2 in order to describe the concepts of cryptography and cryptanalysis. Keywords: Steganography, Least Significant Bit (LSB), Cryptool2